1
$\begingroup$

I want to evaluate the following function:

$$x\left|{\log{\left(x+1\right)}}\right|$$

for $x\rightarrow(-1)^+$.

This is what I'm doing. Since $\left|{\log{\left(x+1\right)}}\right|$ is a negative quantity that approaches $-\infty$ for $x\rightarrow(-1)^+$ we have that:

$$x\left|{\log{\left(x+1\right)}}\right|=-x\log{\left(x+1\right)}$$

Now we have that $x+1\rightarrow0$ for $x\rightarrow(-1)^+$ therefore $\log{\left({x+1}\right)}\sim x+1$

This should mean that

$$f(x)\sim -x\left({x+1}\right)\sim -(-1)(x+1)=x+1\rightarrow0^-$$

However my texbook reports that the limit is actually $-\infty$. Any hints on what I did wrong?

$\endgroup$
2
$\begingroup$

The following does not hold : $\log x \sim x$ as $x \to 0$.

Now, the limit should be :

$$\lim_{x \to -1^+} x|\log(x+1)| = \lim_{x \to -1^+} -|\log(x+1)| = - \infty$$

since $\log(x+1)$ tends to $-\infty$ for $(x+1) \to 0$.

$\endgroup$
2
$\begingroup$

$$\begin{align} \lim_{x\to(-1)^+}x|\ln (1+x)|&=\lim_{\epsilon\to 0^+}(\epsilon -1)|\ln(\epsilon-1+1)|\\ &=\lim_{\epsilon\to 0^+}(\epsilon -1)|\ln\epsilon|\\ &=-\infty \end{align} $$

$\endgroup$
2
$\begingroup$

It is not true that $\log t \sim t$ as $t \to 0$. To find $\lim_{x\to (-1)^{+}} -x\log (1+x)$ note that $\log (1+x) \to -\infty$ and $-x \to 1$. Just multiply the limits.

$\endgroup$
  • $\begingroup$ This should be a comment, not an answer. $\endgroup$ – uniquesolution Aug 22 '18 at 8:09
  • $\begingroup$ @uniquesolution The OP question was "Any hints on what I did wrong ?". So that's an eligible answer. $\endgroup$ – Rebellos Aug 22 '18 at 8:10
  • $\begingroup$ @Rebellos You are entitled to your opinion. $\endgroup$ – uniquesolution Aug 22 '18 at 8:11
  • 1
    $\begingroup$ Thanks, I didn't see that. This hint helped me $\endgroup$ – Cesare Aug 22 '18 at 8:11
1
$\begingroup$

An option:

$y:= \log (1/(x+1)), y >0$ for

$0> x >-1,$ then

$\lim_{(x+1) \rightarrow 0^+} y= \infty.$

With $e^y:=1/(x+1)$,

$|\log (x+1)|= |\log (1/(x+1))| = |\log e^y|= y.$

$\lim_{(x+1) \rightarrow 0^+} x|\log(1+x)|=$

$\lim_{y \rightarrow \infty}(e^{-y}-1)y= -\infty.$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.